Rootless cone eruption processes informed by dissected tephra deposits and conduits. - Reynolds, P.R.; Brown, R.J.; Thordarson, T.; Llewellin, E.; Fielding, K. (Bulletin of Volcanology, 2015)
Rootless cones result from the explosive interaction between lava flows and underlying water-saturated sediment or volcaniclastic deposits. Rootless explosions can represent a significant far-field hazard during basaltic eruptions, but there are few detailed studies of their deposits. A rootless cone field in the 8.5 Ma Ice Harbor flow field of the Columbia River Basalt Province, NW USA, is revealed by sections through rootless conduit and cone structures. The Ice Harbor lava flow hosting the rootless cones was emplaced across a floodplain or lacustrine environment that had recently been mantled by a layer of silicic volcanic ash from a major explosive eruption. Our observations indicate a two-stage growth model for the rootless cones: (1) initial explosions generated sediment-rich tephra emplaced by fallout and pyroclastic density currents and (2) later weaker explosions that generated spatter-rich fountains. Variable explosive activity resulted in a wide range of pyroclast morphologies and vesicularities. Cross-sections through funnel-shaped conduits also show how the conduits were constructed and stabilised. The growth model is consistent with decreasing water availability with time, as inferred for rootless cones described in Iceland. The Ice Harbor rootless cones provide further lithological data to help distinguish between rootless cone-derived tephra and tephra generated above an erupting dyke.